Tourism Activity Without Equitable Income: The Benefit Capture Gap in Upland West Java, Indonesia - Endah Djuwendah; Tuti Karyani; Elly Rasmikayati; Zumi Saidah; O Hasbiansyah (Global Review of Tourism and Social Sciences, 2026)
Community based agroecotourism is promoted in rural Indonesia as a means of improving livelihoods while supporting environmental conservation and cultural preservation. This study examines who benefits economically from such initiatives through a questionnaire survey of 139 residents involved in agroecotourism across four villages in Bandung Regency, West Java. Sustainability was assessed across six dimensions and disaggregated by village, sex, and principal occupation. The findings reveal a benefit capture gap. Although social, cultural, ecological, and technological sustainability received moderate scores, economic sustainability remained the weakest dimension. Perceived improvement in monthly household income was the lowest rated economic attribute, despite favourable assessments of job creation and business diversification. Women, housewives, traders, and respondents in other occupations reported comparatively lower economic indices, whereas farmers and village officials reported higher scores. Weak benefit sharing arrangements and limited formal partnerships may contribute to this pattern. The study recommends prioritising market access, transparent benefit sharing, and targeted inclusion.